Dynamics of athletes choreographic preparedness levelat the stage of specialized basic training (on the basis of sports aerobics) - Valentуna Todorova (Kharkiv State Academy of Physical Culture, 2017)
Article shows the effectiveness of the author's program of choreographic training at the stage of specialized basic training in sports aerobics. Purpose: revealing changes in the level of choreographic preparedness of young athletes at the stage of specialized basic training. Material & Methods: method of expert evaluation, statistical methods of research. Results: a methodology for assessing the choreographic preparedness of athletes at the stage of specialized basic training was introduced. Objectivity of the methods consisted in counting the indices of choreographic readiness. On the basis of the data obtained, it was established that in the experimental group of gymnasts a significant increase in the choreographic skill took place, which was recorded by the group indicator of the formation of the choreographic readiness, and also by all the criteria for choreographic readiness. Conclusion: experimentally proved the effectiveness of the introduction of the author's program of choreographic training in the training process of gymnastics at the stage of specialized basic training to improve their choreographic skills.